Ethyl biodiesel production from non-edible oils of Balanites aegyptiaca, Azadirachta indica, and Jatropha curcas seeds – Laboratory scale development. (October 2016) - Nitièma-Yefanova, Svitlana; Coniglio, Lucie; Schneider, Raphaël; Nébié, Roger H.C.; Bonzi-Coulibaly, Yvonne L.
Abstract: By starting first at the laboratory scale, optimal operating conditions for the reaction unit aimed at producing ethyl biodiesels from non-edible vegetable oils (NEVO) were determined with the ultimate objective of proposing an on-farm processing technology that should be sustainable for emerging countries. Three NEVO widely available in Burkina Faso were selected: Balanites aegyptiaca (BA), Azadirachta indica (AI), and Jatropha curcas (JC) oils. Their conversion to fatty acid ethyl esters (FAEE) was conducted via a two-stage procedure under atmospheric pressure: an alkali-catalyzed ethanolysis at ambient temperature for the BA and AI oils (leading to 93 and 87 wt.% FAEE respectively) and an acid-catalyzed ethanolysis at the normal boiling of the alcohol for the JC oil (leading to 89 wt.% FAEE). Based on the intermediate addition of glycerol at ambient temperature, the two-stage procedure combines chemical kinetics, chemical equilibrium, and phase equilibrium phenomena. Graphical abstract: Highlights: Three non-edible vegetable oils were converted in ethyl biodiesels. A two-stage procedure is used (only one catalyst with intermediate addition of glycerol). The procedure uses the coupling of the involved kinetic and thermodynamic phenomena. The proposal: a compromise between high yields and low energy and material inputs.